Nonprofit governance : (Routledge, 2014)
The current fashion for rolling back the state has seen the nonprofit or third sector playing an increasing role in what were previously the heartlands of the public sphere. This collection offers a comprehensive assessment of research on the governance of nonprofit organisations.